2017
DOI: 10.3389/fpls.2017.01267
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomic View on the Role of Legume Symbiotic Interactions

Abstract: Legume plants are key elements in sustainable agriculture and represent a significant source of plant-based protein for humans and animal feed worldwide. One specific feature of the family is the ability to establish nitrogen-fixing symbiosis with Rhizobium bacteria. Additionally, like most vascular flowering plants, legumes are able to form a mutualistic endosymbiosis with arbuscular mycorrhizal (AM) fungi. These beneficial associations can enhance the plant resistance to biotic and abiotic stresses. Understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 119 publications
0
20
0
Order By: Relevance
“…Rhizobia, which are associated with nodule formation in legume plants, supply nitrogen to the host plants, and can also exist in non-legume plants as beneficial endophytes [6,7]. These rhizobia play important roles in low-input agriculture, land reclamation, and saline soil restoration [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Rhizobia, which are associated with nodule formation in legume plants, supply nitrogen to the host plants, and can also exist in non-legume plants as beneficial endophytes [6,7]. These rhizobia play important roles in low-input agriculture, land reclamation, and saline soil restoration [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In the tripartite mycorrhiza-legume-Rhizobium symbiotic associations in particular, the acquisitions and allocations of N and P are indeed dependent on a complex set of exchanges between rhizobia, mycorrhizal fungi and their root association [32]. Several studies have demonstrated that their inoculation improves growth and productivity of legume plants under a variety of stress conditions [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have revealed how the proteome changes during symbiotic development, and they complement and extend conclusions generated using transcriptomics. A more detailed review on the use of proteomics to characterize the symbiosis was recently published (Larrainzar and Wienkoop 2017).…”
Section: Proteome Studies Of Rhizobiamentioning
confidence: 99%